2021
DOI: 10.1002/cbin.11545
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inflammatory factors and their inhibitors on the hematopoietic stem cells fate

Abstract: Inflammatory cytokines exert different effects on hematopoietic stem cells (HSCs), lead to the development of various cell lineages in bone marrow (BM) and are thus a differentiation axis for HSCs. The content used in this article has been obtained by searching PubMed database and Google Scholar search engine of English‐language articles (1995–2020) using “Hematopoietic stem cell,” “Inflammatory cytokine,” “Homeostasis,” and “Myelopoiesis.” Inflammatory cytokines are involved in the differentiation and prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 129 publications
(157 reference statements)
0
5
0
Order By: Relevance
“…Exposure to tumor cells alters the composition of cytokines produced by host NK cells and several of these cytokines are recognized to influence hematopoiesis. 18–20 We; therefore, hypothesized that the cytokine-profile of NK cells is involved in the observed hematopoietic alterations. Principal component analysis of the intracellular cytokine FACS (Fluorescence-Activated Cell Sorting) staining revealed that splenic NK cells share greater homology to tumorous NK cells as compared with those in bone marrow and peripheral blood ( figure 1H ).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to tumor cells alters the composition of cytokines produced by host NK cells and several of these cytokines are recognized to influence hematopoiesis. 18–20 We; therefore, hypothesized that the cytokine-profile of NK cells is involved in the observed hematopoietic alterations. Principal component analysis of the intracellular cytokine FACS (Fluorescence-Activated Cell Sorting) staining revealed that splenic NK cells share greater homology to tumorous NK cells as compared with those in bone marrow and peripheral blood ( figure 1H ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that stimulation with proinflammatory cytokines such as IL-6 and IL-8 on HSPC, primarily secreted by MSCs in the bone marrow niche, promotes the proliferation and differentiation of HSPCs, thereby facilitating their extravasation. These processes influence the response to chemotactic and adhesion stimuli, which are characteristic of primitive hematopoietic progenitor cells [34]. On the other hand, it has been described that the presence of high oxygen concentrations in the bone marrow niche enhances migration away from the bone marrow, progressively diminishing the primitiveness of HSPCs [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…One of the main challenges during the ex vivo expansion processes of HSPCs is the activation of cellular differentiation mechanisms, leading to changes in the capacity and timing of hematopoietic regeneration once the cells have been transplanted [8,34,37]. The evaluation of the expression of markers related to the primitiveness of CD34+ HSPCs showed that the expression of this marker tends to decrease after the expansion process, with slightly higher expression in the case of co-culture with MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The functions of miRNAs in cancer, inflammation, and immunity have been studied in several researches [16,17]. New researches have shown that miRNA profiles, including circulating miRNAs and those related to cancer or inflammatory process, can be defined from blood [18,19]. Circulating miRNAs are important markers for common diseases because they are relevant to human blood in a surprisingly stable state, and the findings may have a high degree of individual reproducibility [1,20].…”
Section: Micrornas and Obesitymentioning
confidence: 99%